Investigation of the Effects of Welding Path Patterns on the Mechanical Properties of 6061 Aluminum Alloy in GMAW Using a Robotic Welding Arm - Sririkun, Witthaya; Phetsuwan, Wikanet; Sani, Suhaidee; Rawangwong, Surasit; Burapa, Romadorn (Journal of Manufacturing & Management Technology, 2025)
This research aims to investigate the effects of welding path patterns on the mechanical properties of aluminum alloy 6061 under an automated welding process. The study utilizes a robotic welding arm integrated with welding power source, operating under the Gas Metal Arc Welding (GMAW) process, also known as Metal Inert Gas (MIG) welding. The test specimens are aluminum alloy 6061 plates with dimensions of 100 × 200 × 4 mm. Constant welding parameters are maintained, including a welding current of 180 A, shielding gas flow rate of 12 L/min, wire feed speed of 6 m/min, and travel speed of 0.5 m/min. Three distinct welding path patterns are examined: linear (without weaving), zigzag weaving, and circular weaving. Mechanical properties are evaluated using the Vickers Hardness Test and Tensile Test. The results indicate that the circular weaving pattern yields the highest average weld hardness of 70.38 HV and the highest tensile strength of 154.74 MPa. The zigzag weaving pattern follows with a hardness of 64.10 HV and tensile strength of 141.39 MPa, while the linear pattern produces the lowest values at 66.94 HV and 135.44 MPa, respectively. These findings demonstrate that the welding path pattern significantly influences the mechanical behavior of the weld in aluminum alloy 6061. The research findings can be used as a guideline for developing control strategies in robotic welding processes within the industrial sector to enhance the efficiency and quality of welded components.